Propulsive Motion of Cylindrical Vibration-Driven Robot in a Viscous Fluid - V. D. Anisimov; A. G. Egorov; A. N. Nuriev; O. N. Zaitseva (Учёные записки Казанского университета: Серия Физико-математические науки)
The propulsive motion of a multimass system, vibration-driven robot (VR), in a viscous incompressible ﬂuid was studied. The VR consisted of a round cylindrical body submerged in the ﬂuid and an internal mass (IM) performing small-amplitude pendulum-like oscillations inside the body. Using the method of asymptotic expansions, the combined mechanical and hydrodynamic problems that describe the self-propulsion of the system in the ﬂuid were solved. The hydrodynamic problem was formulated on the basis of the complete non-stationary Navier– Stokes equation. An analytical solution was derived to describe the cruising regime of the VR motion in the ﬂuid. The non-stationary hydrodynamic inﬂuence on the VR was determined. The eﬃciency of the propulsive system’s motion was assessed.